Potency of spirulina (Spirulina platensis) on arsenic-induced lipid peroxidation in rat - Khair, Abul; Awal, Md Abdul; Islam, Md Shafiqul; Islam, Md Zahorul; Rao, Damanna R (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Natural substances found in dietary sources and medicinal plants have attracted considerable attention in recent years as chemopreventive agents. Spirulina is a blue-green alga that possesses chemopreventive properties. The purpose of this study was to determine the effect of spirulina on rats with inorganic arsenic (As) [sodium arsenite (NaAsO2)]-induced lipid peroxidation. Materials and Methods: 120 rats were randomly assigned to 10 groups and designated T0, T1, T2, T3, T4, T5, T6, T7, T8, and T9. One group was kept as a control (T0) that received no treatment. The seven groups received 3.0 mg of NaAsO2/kg body weight in drinking water and were given spirulina ad libitum. T1 was treated with NaAsO2 but not with spirulina. Two groups of rats (T2 and T3), on the other hand, were treated with spirulina without receiving any As (NaAsO2). T2 received agro-based spirulina (Ab-Sp; grown in 1.5% soybean meal media and harvested on day 12 of seed inoculation) at 2.0 gm/kg feed, whereas T3 received commercially available spirulina (Com-Sp) at 2.0 gm/kg feed. T4, T5, and T6 were concurrently treated with Ab-Sp at 1.0, 1.5, and 2.0 gm/ kg of feed. On the other hand, T7, T8, and T9 induced by NaAsO2 were concurrently treated with Com-Sp at 1.0, 1.5, and 2.0 gm/kg feed. All groups received treatment for 90 days. Results: The efficacy of both spirulina in preventing lipid peroxidation caused by As was determined quantitatively by measuring the rats’ serum malondialdehyde (MDA). The results indicated that As supplementation increased serum MDA levels, whereas both types of spirulina significantly decreased them. The highest dose of Ab-Sp (2.0 gm/kg feed) was found to be the most effective in preventing lipid peroxidation in rats treated with inorganic As. Conclusion: Ab-Sp could be a natural, cost-effective, and safe measure to mitigate As toxicity. J. Adv. Vet. Anim. Res., 8(2): 330-338, June 2021